Longitudinal study of the Drowning Prevention Knowledge Level of schoolchildren in Rio de Janeiro, Brazil (International Seven Journal of Health Research, 2024)
Drowning is quick, silent and recognized as a serious public health problem worldwide, but it is neglected. Children and adolescents receive insufficient education about drowning prevention. The objective of this study was to monitor changes in the Drowning Prevention Knowledge Level (DPKL) in elementary school children and adolescents at CAp-UERJ, Rio de Janeiro, Brazil. The methodology was a longitudinal study carried out from 2022 to 2024 with students from the (5th, 6th, 7th, 8th and 9th years) of CAp-UERJ. 12 classes were monitored until 2024, totaling 336 students, four of which were in the 7th year, four in the 8th year and four in the 9th year, with a total of 112 students per year of schooling. A structured questionnaire divided into three parts containing 20 items about DPKL was answered at the school. In the 1st part, students correlated the universal figures used on signs to prevent drowning with the texts that signify those images (7 questions), in the 2nd part they had to relate the colors of the green, yellow and red flags and their meaning in regarding bathing conditions (3 questions) and in the last part, the student marked yes or no on statements related to the correct behavior to be adopted in the aquatic environment (10 questions). Each class received 3 interventions based on the individual DPKL result. When all years of schooling were analyzed together in three moments (2022, 2023 and 2024), the result showed that there was an improvement in knowledge about the 7 prevention signs, to the point that 99.1% of students now knew the meanings of the signs, and in two of them, sign no. 2, which refers to the emergency telephone and in no. 3, pushing prohibited, there was 100% accuracy. It was also possible to verify that after the intervention, almost all (98%) of the students correctly understood the meaning of the colors of the green, yellow and red flags. Regarding the behavior of playing nearby or putting their hand in the drain that sucks water from the pool, the result showed that the youngest were the ones who improved the most after intervention, going from 77.2% to 99.1% of those who responded correctly in 2024; about entering the pool, diving with a “somersault”, in a dangerous and inappropriate way, it was found that the older they were, the more aware of the danger caused by headfirst dives. Regarding the DPKL categorization, it was noted that 99% of students were classified as DPKL excellent in 2024. Those in the 8th and 9th years obtained 100% in the classification as DPKL excellent. It can be concluded that the school was a good place to carry out preventive interventions on drowning using an approach focused on behavior change, conceptual identification and student awareness in order to improve DPKL. The diagnostic use of DPKL to monitor school-age students can help identify safety values and concepts in certain regions of the country or specific groups that are not familiar with aquatic environments and thus help to formulate preventive interventions if necessary.